The Impact of Marketing Communication in Attracting Customer (Case Study at Fairmont Hotel Jakarta) - Natakusumah, Yuan Reza Maulana; Nursiana, Adinoto; Suryono, Chondro (Institut Pariwisata Trisakti, 2017)
Fairmont Hotel Jakarta has the unstable occupancy from month to month, started from January to December 2016. The objective of this research is to know the impact of marketing communication in attracting customer at Fairmont Hotel Jakarta. This research used associative casual. Population are all the guests who stayed in Fairmont Hotel Jakarta in the year of 2016. The sampling technique is non-probability sampling, and used incidental sample. The number of sample in this research is 120 respondents. Data was collected by distributing questionnaires with Likert scale. The statements in the questionnaires were tested of their validity and reliability. The data was analysed by using SPSS 19.0. The study found that marketing communication that consisted of advertising, sales promotion, public relation, personal selling and direct marketing impacted to attract customers 22,9%.